If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 3) + -6(-2x + 1) = 9(x + -2) Reorder the terms: 5(3 + 2x) + -6(-2x + 1) = 9(x + -2) (3 * 5 + 2x * 5) + -6(-2x + 1) = 9(x + -2) (15 + 10x) + -6(-2x + 1) = 9(x + -2) Reorder the terms: 15 + 10x + -6(1 + -2x) = 9(x + -2) 15 + 10x + (1 * -6 + -2x * -6) = 9(x + -2) 15 + 10x + (-6 + 12x) = 9(x + -2) Reorder the terms: 15 + -6 + 10x + 12x = 9(x + -2) Combine like terms: 15 + -6 = 9 9 + 10x + 12x = 9(x + -2) Combine like terms: 10x + 12x = 22x 9 + 22x = 9(x + -2) Reorder the terms: 9 + 22x = 9(-2 + x) 9 + 22x = (-2 * 9 + x * 9) 9 + 22x = (-18 + 9x) Solving 9 + 22x = -18 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 22x + -9x = -18 + 9x + -9x Combine like terms: 22x + -9x = 13x 9 + 13x = -18 + 9x + -9x Combine like terms: 9x + -9x = 0 9 + 13x = -18 + 0 9 + 13x = -18 Add '-9' to each side of the equation. 9 + -9 + 13x = -18 + -9 Combine like terms: 9 + -9 = 0 0 + 13x = -18 + -9 13x = -18 + -9 Combine like terms: -18 + -9 = -27 13x = -27 Divide each side by '13'. x = -2.076923077 Simplifying x = -2.076923077
| 2[x-2(x-1)]-3(3y-5)=-11 | | (2x-5)2-(x+1)2=7x | | -5(2t+2)=20 | | n+(-12)=3n | | X-2x+3=4x+2 | | 9x-9=9-8x | | 8x-16-2x=34 | | 12ab-28bc+20ac=0 | | x^(2/#)=1/3 | | 10x=0.000001 | | 3t^2-16t+21=0 | | -2x-6y+11=-11 | | 4n+21=-3 | | q^2+75q-6250=p | | q^2+75q-6250=q | | 4n^2-x-2000=0 | | 2x^2+6x-77=0 | | -3=6-x/9=3 | | -16times-0.15=x | | 6b(2a-3c)-5d(2a-3c)=0 | | 6(3s+6)=216 | | X-17=x+51 | | 3(x+10)=(2x+30) | | -16x-0.15=f | | 4(2l+5)=92 | | q^2+75q-6250=0 | | 0.51(2x)=x+1 | | (2x-1)(3x-1)=(6x+2)(x-4) | | 2x-9/5=x+18 | | g^2*10g^3-2g^3+g^5=0 | | 6x^2-x-1000=0 | | 5(a-5)=80 |